We Are (Not) the Virus: Competing Online Discourses of Human-Environment Interaction in the Era of COVID-19. Issue 3 (3rd April 2023) - Fine, Julia C.; Love-Nichols, Jessica
ABSTRACT: Previous research has found that social media may be a particularly influential means of circulating ideologies about climate justice. In this article, we analyze social media discourses of universal human responsibility for pollution and ecosystem destruction during the COVID-19 pandemic, epitomized by the viral hashtag #WeAreTheVirus. We then examine three types of counterdiscourses that oppose misinformation and false universalization of human responsibility. These counterdiscourses include: (1) metadiscourses of ecofascism and racial injustice, (2) counterslogans that ascribe responsibility to systemic injustice rather than individual humans (e.g. "Capitalism is the virus, " "The system is the virus"), and (3) memes that parody the #WeAreTheVirus discourses (as in the sarcastic phrase "Nature is healing, we are the virus"). We demonstrate that the former two nonparodic counterdiscourses emerged in part in the comments of #WeAreTheVirus Tweets, while the parodic memes emerged in separate Tweets, which were a site of shared humor rather than controversy. We further demonstrate that, while both #WeAreTheVirus discourses and counterdiscourses have occurred relatively rarely since their period of virality and have broadened to a range of domains outside of human-environment interaction, counterdiscourses have nevertheless had a wide-ranging impact, increasing metadiscourses of ecofascism and permeating material landscapes through graffiti and signage.